2020
DOI: 10.1038/s41598-020-57756-7
|View full text |Cite
|
Sign up to set email alerts
|

The ubiquitin ligase HERC1 regulates cell migration via RAF-dependent regulation of MKK3/p38 signaling

Abstract: Protein modifications by phosphorylation or ubiquitylation have been selected throughout evolution as efficient regulatory mechanisms of cellular processes. Cell migration is a complex, highly coordinated process where these mechanisms must participate in an integrated manner to transmit signaling during migration. In this study, we show that the ubiquitin ligase HERC1 regulates the p38 signaling pathway, and that this regulation is mediated by the MAPK kinase MKK3. Moreover, we demonstrate a crosstalk between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 26 publications
2
21
0
Order By: Relevance
“…Our in vitro validation experiments showed that HERC1 depletion did not affect cell proliferation but directly inhibited cellular migration in Boyden chamber and wound healing assays, as well as invasion. In the course of our studies, Herc1 was reported as a regulator of migration, further supporting our findings [44].…”
Section: Discussionsupporting
confidence: 91%
“…Our in vitro validation experiments showed that HERC1 depletion did not affect cell proliferation but directly inhibited cellular migration in Boyden chamber and wound healing assays, as well as invasion. In the course of our studies, Herc1 was reported as a regulator of migration, further supporting our findings [44].…”
Section: Discussionsupporting
confidence: 91%
“…Our in vitro validation experiments showed that HERC1 depletion did not affect cell proliferation but directly inhibited cellular migration in Boyden chamber and wound healing assays, as well as invasion. In the course of our studies, Herc1 was reported as a regulator of migration, further supporting our findings (34).…”
Section: Discussionsupporting
confidence: 91%
“…However, studies have also found that activating p38 promotes cell migration. In the ubiquitin ligase HERC1-depleted cells, for example, activation of p38 increases the migration of human osteosarcoma U2OS cells [52]. These findings suggest that various stimulants affect cell migration through specific signaling pathways.…”
Section: Discussionmentioning
confidence: 92%